An essential role of acetyl coenzyme A in the catalytic cycle of insect arylalkylamine N-acetyltransferase - Chu-Ya Wu (Nature Portfolio, 2020)
Wu et al. provide insight to the role of acetyl coenzyme A in regulating N-acetylation in insect AANAT using ITC and NMR methods. These results provide useful data on the structural function of insect AANATs.